The Islamic State a brief introduction - Lister, Charles R. 1987- (Brookings Institution Press, 2015)
In 2014, the Islamic state seemingly appeared out of nowhere, routing Iraqi forces, conquering Iraq's second-largest city, boldly announcing the establishment of a caliphate, and declaring itself the Islamic State (IS). In this definitive guide to the Islamic State and its senior leadership, Charles R. Lister traces its roots from the release of its notorious father figure, Abu Musab al-Zarqawi, from a Jordanian prison and the group's formation in Afghanistan in the late-1990s, and finally to its stunning maturation in Iraq and Syria. The West knows IS through its unrelenting propaganda war. Behind the deft use of social media and the slick videos of despicable acts is what amounts to a proto-state. Lister shares details of IS's sophisticated revenue machine, attempts at governing, and its formidable military. With IS knocking on the doors of Lebanon, Jordan, and Saudi Arabia, Lister's portrait helps us understand what to expect next and recommends a course of action to defeat IS, extinguish extremism, and encourage a tolerant Islam across the Middle East.